2013
DOI: 10.1007/s11548-012-0811-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided facet joint injection training using Perk Tutor

Abstract: The results of this pilot study suggest that Perk Tutor provides an improved training environment for US-guided facet joint injections on a synthetic model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…The Perk Station [4143] is a training platform for image-guided interventions. While training on a phantom, trainees perform tasks using AR image overlay.…”
Section: Resultsmentioning
confidence: 99%
“…The Perk Station [4143] is a training platform for image-guided interventions. While training on a phantom, trainees perform tasks using AR image overlay.…”
Section: Resultsmentioning
confidence: 99%
“…All eight insertions into the facet joint were deemed technically successful by the expert spine surgeon (needle tip in the gap between the articular processes [7]), with average orthogonal positioning errors for robotic and conventional way of guidance of 1.36 ± 0. 33 tively.…”
Section: Needle Insertion Accuracymentioning
confidence: 99%
“…While the cumbersome procedure induces a slow learning curve [6,7], work-related musculoskeletal disorders have been associated with medical sonographers [8], impeding the quality of USbased interventions over time. Both of these issues relate to the freehand nature of previous US-guided facet joint injections, suggesting more automated solutions [9].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the Perk Tutor was shown to be beneficial in teaching novices to use ultrasound to guide spinal facet joint injections. 9,10 We designed a randomized controlled trial to determine if Perk Tutor could help residents learn to use ultrasound to guide LP in simulation phantoms with abnormal spinal anatomy. Real-time needle position tracking was used as a measure of needle movement within tissue.…”
Section: Résumémentioning
confidence: 99%